Analisis Hubungan Antar Pekerjaan pada Proyek Rumah Tinggal dengan Perencanaan Microsoft Project: (Studi Kasus Proyek Pembangunan Rumah Tinggal, Kecamatan Balikpapan Selatan, Kota Balikpapan, Kalimantan Timur) - Monica Gurning; Gunaedy Utomo; Reno Pratiwi (SENTRI: Jurnal Riset Ilmiah, 2026)
Every construction project has specific targets that must be achieved at each stage of its planning. Within such a project, there exists a series of interrelated work activities, each with defined completion limits. Therefore, the initial and most crucial step is to develop a well-structured plan to ensure that project implementation can be properly controlled using an appropriate scheduling method. One method that can be applied is the Precedence Diagram Method (PDM), which provides detailed information related to project activities, including start time, duration, finish time, and total float, represented within interconnected rectangular nodes through various types of dependency relationships. This method enables the identification of activities that have the potential to cause delays if postponed, thereby forming the critical path that determines the overall project success. Along with technological advancements, project scheduling has become more efficient with the aid of specialized software such as Microsoft Project, which in this study is utilized to implement the PDM method in analyzing interrelated project activities. In this project scheduling, there are 175 constraints consisting of 73 Start-to-Start (SS), 101 Finish-to-Start (FS), and 1 Finish-to-Finish (FF) relationship. A total of 55 activities are identified as part of the critical path, indicating that any delay in these activities will directly impact the overall project completion time.